A Proposed Approach for Monitoring Information Systems Projects - Oweeda Basel; Khalaf Majeedy (المجلة الدولية للحاسبات والمعلوماتية, 2023)
This paper aims to evaluate the performance of Information Systems Project Management (ISPM). It clarifies the relationships between ISPM domains, performance metrics, and performance indicators. This paper presents a proposed list of metrics for ISPM. Based on these ISPM metrics and a combination of statistical techniques, we built a model for calculating ISPM performance indicators. The quality reviewers can use this model to evaluate and track the performance of IS project managers.